Donor‐derived cell‐free DNA as a biomarker for rejection after kidney transplantation: a systematic review and meta‐analysis. (14th October 2020) - Wijtvliet, Veerle P. W. M.; Plaeke, Philip; Abrams, Steven; Hens, Niel; Gielis, Els M.; Hellemans, Rachel; Massart, Annick; Hesselink, Dennis A.; De Winter, Benedicte Y.; Abramowicz, Daniel; Ledeganck, Kristien J.
Summary: A systematic review and meta‐analysis were performed to investigate the value of donor‐derived cell‐free DNA (dd‐cfDNA) as a noninvasive biomarker in diagnosing kidney allograft rejection. We searched PubMed, Web of Science and the Cochrane Library for original research papers published between January 1994 and May 2020 on dd‐cfDNA fractions in blood of kidney allograft recipients. A single‐group meta‐analysis was performed by computing pooled estimates for dd‐cfDNA fractions using the weighted median of medians or quantile estimation (QE) approach. Weighted median differences in medians (WMDMs) and median differences based on the QE method were used for pairwise comparisons. Despite heterogeneity among the selected studies, the meta‐analysis revealed significantly higher median dd‐cfDNA fractions in patients with antibody‐mediated rejection (ABMR) than patients without rejection or patients with stable graft function. When comparing patients with T cell‐mediated rejection (TCMR) and patients with ABMR, our two statistical approaches revealed conflicting results. Patients with TCMR did not have different median dd‐cfDNA fractions than patients without rejection or patients with stable graft function. dd‐cfDNA may be a useful marker for ABMR, but probably not for TCMR.